Evaluating the Performance of Cluster Frontline Demonstration (CFLD) on Mustard in North Bengal (Indian Journal of Extension Education, 2025)
The production and productivity of mustard in terai and dooars region of North Bengal was comparatively low than national and state average, and farmers were still following decade old varieties and traditional practices. Hence, IARI regional station-Kalimpong promoted advance mustard varieties like PM 30, PM 26 and Pusa Vijay in the region through 600 CFLDs in 6 blocks of Jalpaiguri, Kalimpong and Darjeeling district in North Bengal. The demonstrations were conducted in five consecutive rabi seasons from 2019- 2023 and their performance were assessed each year against the control variety. The study used a mix of control- treatment and before-after experimental research design. The findings revealed that the maximum yield was recorded in Pusa Vijay (18.60 q/ha) followed by PM 26 (17.30 q/ha) and PM 30 (13.80 q/ha). The Pusa Vijay reported yield advantage of 48.92 per cent followed by PM 26 (45.09%) and PM-30 (31.16%). The study proved the effectiveness of CFLD in speedy outspread of suggested technologies of mustard horizontally among the farming communities. So, it is recommended that policy bodies should come up with sufficient financial support to frontline extension system for conducting CFLD under the guidance of scientists and extension professionals.